Empowerment of Abandoned Ponds for Sustainable Mangrove Rehabilitation Activities in Percut Sei Tuan, Deli Serdang, Indonesia - Mohammad Basyuni; Rizka Amelia; Dwi Suryanto; Ipanna Enggar Susetya; Yuntha Bimantara (Talenta Publisher, 2022)
Mangrove ecosystems provide important functions for ecosystem service. However, the degradation of mangrove forests, especially conversion to aquaculture ponds is a driver for deforestation. Therefore, this study aimed to analyze the mangrove vegetation and duration of inundation in ponds before and after rehabilitation activities were conducted on abandoned ponds. In this analysis, we used the census method to collect structural data, the Important Value Index (IVI), composition and structure, and the diversity index. To determine the duration of inundation at the observation sites in a pond in Tanjung Rejo, Percut Sei Tuan village, we deployed one water logger and two Mini Buoys at ponds. At the observation site, eight pure mangrove species have been founded, namely Avicennia alba, A. marina, Bruguiera gymnorrhiza, Excoecaria agallocha, Rhizophora apiculata, R. mucronata, R. stylosa, and Nypa fruticans. The main species was A. marina which is a total of 756 idv/ha at the seedling stage 52.81 idv/ha at the sapling stage, and 268.09 idv/ha at the tree level. The highest IVI has founded in seedlings, saplings, and trees at A. marina, which was 99.30%. 80.41% and 94.49%, respectively. Rehabilitated Avicennia spp that grew only 2.4% from 2000 seedlings. The low growth of seedlings was influenced by the pond condition which was always in a state of flooding. The current study provides important information that in carrying out planting or rehabilitation activities it is necessary to determine which inundation rotation should be a priority considered.